2022
DOI: 10.1155/2022/2213207
|View full text |Cite|
|
Sign up to set email alerts
|

Internet of Things Application of Intelligent and Innovative Learning Strategies in the Higher English Education System

Abstract: In order to improve the effect of higher English teaching, this paper builds a higher English education system based on Internet of Things technology. The optimization aim of this study is to provide an online DRX parameter optimization technique that is compatible with the RRC protocol architecture. This work employs algorithms based on reinforcement learning to accomplish parameter optimization and dynamic control by selecting optimal DRX parameters and dynamically configuring them via decision-making proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…During the implementation of the project, teachers should encourage students to actively participate and interact with each other. Students can cooperate through joint discussion, joint creation, and joint rehearsal [5] . In the process, they will not only be able to improve their musical skills, but also develop teamwork, innovative thinking and problem-solving skills.…”
Section: Establishment Of Music Project Practice and Evaluation Feedb...mentioning
confidence: 99%
“…During the implementation of the project, teachers should encourage students to actively participate and interact with each other. Students can cooperate through joint discussion, joint creation, and joint rehearsal [5] . In the process, they will not only be able to improve their musical skills, but also develop teamwork, innovative thinking and problem-solving skills.…”
Section: Establishment Of Music Project Practice and Evaluation Feedb...mentioning
confidence: 99%
“…e main tools adopted include: a questionnaire of learning strategy based on learning strategy, discussion with senior English teachers in colleges and universities, etc. e effect of English classroom teaching will indirectly affect students' English reading and writing ability [7,8]. English classes pay attention to skills and practice, how to enhance students' communicative consciousness should be given priority, students dare to speak, dare to express their ideas is the fundamental purpose of English learning.…”
Section: Introductionmentioning
confidence: 99%
“…Security and Communication Networks has retracted the article titled "Internet of Tings Application of Intelligent and Innovative Learning Strategies in the Higher English Education System" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%